Negative Acoustic Reflex: An Unusual Finding - Samuel JD; Gopal HS; Radha MA; Sudha K Murthy (Journal of All India Institute of Speech and Hearing, 1970)
The sensitivity of the audiplogical test battery has been greatly enhanced with the introduction of impedance  audiometry (Hodgson,1978). Acoustic reflex testing, a part of impedance battery is a reliable diagnostic indicator of various lesions in the auditory system (Wilber and Feldman, 1976)